POPULATIONS AND HELMINTOFAUNA OF BARSSICS IN THE CONDITIONS OF KARAKALPAKSTAN - Kizilbaeva, Kumisay Saparbaevna (SCIENCE and SOCIETY, 2026)
Helminthological studies were conducted on 25 wild badgers. According to the research results, 16 species of helminths were recorded in badgers, which belong to 3 types, 4 classes, 8 orders, 12 families, and 14 genera. Of these, 3 species of cestodes, 1 species of trematodes, 3 species of acanthocephalans, and 9 species of nematodes were identified.